Physiological regulation of peroxisome proliferator-activated receptor-gamma coactivator 1 alpha in mitochondrial metabolism during physical exercises: a systematic review - Ayubi , N.; Wibawa, J.C.; Rizki, A.Z.; Afandi, A.; Callixte, C. (Medicni Perspektivi, 2025)
This study aims to analyze in depth the mechanism of physical exercises in increasing the expression of PGC-1α (peroxisome proliferator-activated receptor gamma coactivator 1-alpha) as the most important part of mitochondrial biogenesis through a systematic review. Literature databases including PubMed, Web of Science, and Science Direct were searched for this systematic review study. The inclusion criteria for this study were articles published in the last five years. The articles discussed PGC-1α, exercises, and mitochondrial biogenesis. PubMed, Web of Science, and Science Direct databases were used to find 141 published articles. Finally, 13 articles that met the inclusion criteria were selected and analyzed for this systematic review. In this study, standard operating procedures were evaluated using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Exercises have been shown to increase PGC-1α expression, according to this systematic review. Increased biogenesis in mitochondria may be triggered by increased PGC-1α expression, which helps in the energy production process. On the other hand, it is not yet clear about the ideal intensity and type of physical activity to increase PGC-1α. This provides recommendations for further exploration in future experimental studies.